1998
DOI: 10.1038/sj.bjp.0701719
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sympathetic noradrenergic neurotransmission in the tail artery of Donryu rats fed with high cholesterol‐supplemented diet

Abstract: 1 Sympathetic neurotransmission and noradrenaline content of the tail artery of Donryu rats fed for 2 months with a cholesterol-supplemented diet enriched with 4% cholesterol, 1% cholic acid, 0.5% thiouracil (CCT), were examined. 2 Total serum cholesterol level of CCT fed rats (7.05+1.77 mg ml 71 , n=8) was signi®cantly greater than lab-chow fed controls (2.58+0.32 mg ml 71 , n=8). Low density lipoprotein level was also signi®cantly increased in CCT-fed (1.79+0.26 mg ml 71 , n=8) compared with control fed rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…2,42,43 In agreement with previous studies, 3,44 we also found that the contractile responses to KCl and phenylephrine were not altered in the aortas and carotid arteries taken from ApoE Ϫ/Ϫ mice. In addition, our data show that chronic fluvastatin treatment significantly enhances the contractile vascular responses to KCl and phenylephrine of carotid and aorta from ApoE Ϫ/Ϫ mice but not from WT mice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2,42,43 In agreement with previous studies, 3,44 we also found that the contractile responses to KCl and phenylephrine were not altered in the aortas and carotid arteries taken from ApoE Ϫ/Ϫ mice. In addition, our data show that chronic fluvastatin treatment significantly enhances the contractile vascular responses to KCl and phenylephrine of carotid and aorta from ApoE Ϫ/Ϫ mice but not from WT mice.…”
Section: Discussionsupporting
confidence: 81%
“…The consequences of hypercholesterolemia on vascular contractile responses are still controversial, depending on the experimental model used (species, age, diet), 2,40 -42 the vascular preparation, 41,43 and the contracting agent. 2,42,43 In agreement with previous studies, 3,44 we also found that the contractile responses to KCl and phenylephrine were not altered in the aortas and carotid arteries taken from ApoE Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Interestingly, fish oil components increase the release of ATP [ 99 ] and a high cholesterol diet decreases ATP release from arteries [ 100 , 101 ].
Fig.
…”
Section: Atherosclerosismentioning
confidence: 99%
“…2). Interestingly, fish oil components increase the release of ATP [99] and a high cholesterol diet decreases ATP release from arteries [100,101].…”
Section: Atherosclerosismentioning
confidence: 99%